Depletion of UBAP2L suppresses colorectal cancer cell proliferation and radiotherapy resistance by regulating GPX4 - Yueyun Li; Xiansheng Wang; Xiangyan Zhang; Shuchao Zhao; Jiayun Lei; Chang Xu (Journal of Cancer Research and Clinical Oncology)
Abstract Background The aim of this study is to investigate the potential role of UBAP2L in the proliferation and radiotherapy resistance of colorectal (CRC) cells. Methods Clinical and pathological data were collected from 257 patients with stage I–III primary CRC who underwent surgical treatment at the Affiliated Hospital of Qingdao University (Qingdao, China) and Shandong Electric Power Central Hospital (Shandong China) from 2015 to 2019. Additionally, tumor biopsy specimens were collected from 30 patients with locally advanced rectal cancer. The expression of UBAP2L in CRC tissues was tested using immunochemistry. The association of UBAP2L expression with clinicopathological data and outcomes of patients with CRC was determined. Overexpression and knockdown cells were constructed to evaluate the proliferation and radiotherapy resistance of UBAP2L in CRC cells. Results Our results showed UBAP2L was significantly overexpressed in CRC tissues compared to adjacent non-tumor tissues (75.48% vs. 21.01%, P < 0.05). UBAP2L expression is associated with tumor location (P = 0.001), and deeper tumor invasion (T stage, P = 0.001). Survival analysis showed that the disease-free survival of patients with high UBAP2L expression was significantly shorter than that of patients with low UBAP2L expression (P = 0.006). Gain and loss-of-function experiments demonstrated UBAP2L-KD significantly inhibited the proliferation and radio-resistance of CRC cells, while UBAP2L-OE promoted the proliferation and radio-resistance of CRC cells. Moreover, ferrostatin-1 reversed the inhibitory effect of UBAP2L-KD on CRC cell proliferation and radio-resistance, while RSL3 reversed the promoting effect of UBAP2L-OE on CRC cell proliferation and radio-resistance. These findings suggest that UBAP2L regulates CRC cell proliferation and radio-resistance in a GPX4-dependent manner. Conclusion UBAP2L is highly expressed in CRC, and its expression correlates with poor disease-free survival. Depletion of UBAP2L inhibits CRC proliferation and radio-resistance by downregulating GPX4. Therefore, UBAP2L may be a promising therapeutic target for the treatment of CRC.